2014
DOI: 10.1128/jvi.00200-14
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-Electron Microscopy Study of Insect Cell-Expressed Enterovirus 71 and Coxsackievirus A16 Virus-Like Particles Provides a Structural Basis for Vaccine Development

Abstract: Enterovirus 71 (EV71) and coxsackievirus A16 (CA16) are the two most common etiological agents responsible for the epidemics of hand, foot, and mouth disease (HFMD), a childhood illness with occasional severe neurological complications. A number of vaccine candidates against EV71 or CA16 have been reported; however, no vaccine is currently available for clinical use. Here, we generated a secreted version of EV71 and CA16 virus-like particles (VLPs) using a baculovirus-insect cell expression system and reconstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 56 publications
4
30
1
Order By: Relevance
“…Using inoculum, procapsid, or peptide fragments does have the capability of producing neutralizing antibodies (25,48,(52)(53)(54). However, consideration of both antigenic forms of the EV71 capsid is critical.…”
Section: Discussionmentioning
confidence: 99%
“…Using inoculum, procapsid, or peptide fragments does have the capability of producing neutralizing antibodies (25,48,(52)(53)(54). However, consideration of both antigenic forms of the EV71 capsid is critical.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Gong et al reported the cryo-EM structure of EV71 VLP produced in insect cells at 5.2-Å resolution (EMBL-EBI identifier EMD-2607) (19). The crystal structure of our EV71 VLP produced in yeast was fitted into the reported cryo-EM density map ( ϭ 1), which showed that the crystal structure agreed well with the cryo-EM structural features, except for a few protruding loops (cc ϭ 0.81).…”
Section: Ev71-vlp-c4 a S V Pmentioning
confidence: 99%
“…We used UCSF Chimera (18) to visualize the cryo-EM density map of EV71 VLP (EMD-2607) (19), to segment the corresponding density maps, and to compare the structural similarities between electron density and crystal structure of EV71 VLP. After docking the crystal structure of EV71 VLP (PDB ID 4YVS) into the EV71 VLP density map ( ϭ 1.00), the correlation coefficient (cc) values from comparisons of the cryo-EM density map and crystal structure were calculated using "Fit in Map" in UCSF Chimera (18).…”
Section: Figmentioning
confidence: 99%
“…Recently, Ren et al reported crystal structures of the unexpanded CVA16 mature virion, the procapsid, and a recombinant virus-like particle (VLP) (12). In addition, the structure of the insect cell-produced CVA16 VLP has been determined at 5.5 Å by cryo-electron microscopy (cryo-EM) single-particle analysis (13). These studies reveal that the capsid of CVA16 virions is similar to those of other enteroviruses, which is an arrangement of 60 copies of protomers each consisting of 4 subunits known as VP1, VP2, VP3, and VP4.…”
mentioning
confidence: 99%